Flexibility of Interior Spaces for Low Cost Housing in Kenya- A Case Study of the Kibera Soweto East Housing Project in Nairobi, Kenya - Njeru, G. W; Maina, S.; Munene, M (MksU Press, 2021)
Kibera is the largest slum areas in Nairobi and the largest urban slum in Africa (UN-HABITAT, 2008). It‟s characterized by poorly constructed mabati (iron sheet) structures, poor-drainage systems, and lack of clean water, electricity, medical care etc. Most of Kibera slum residents live in extreme poverty, earning less than Ksh. 100 per day. The government of Kenya set up the Kenya Slum Upgrading Program (KENSUP) in 2004 whose main aim was to provide low-cost housing to residents living in the slum areas including Kibera, Mathare, Kayole and Dandora. The Kibera Soweto East Project also dubbed „The Canaan Estate‟ was one of the first projects under the program and comprised of 21 blocks of five floors each sitting in a five-acre piece of land. However in 2017, more than half of the apartments had been given out for renting or sold by the allocated owners and the residents went back to the slum. The major reason for these phenomenon was due economical enrichment. 40% of the residents preferred to rent their houses as means of earning extra income. However, 50% of the residents stated that the houses did not cater for their needs and lifestyles taking into consideration that they now own the houses. The slum houses allows them to manipulate as well as modify their interior spaces, a concept they are not able to implement in their new houses. This is indeed a great challenge due to their rapid growth in population and change in need and lifestyle over time. This study therefore sought to determine how flexible are the interior spaces of the low-cost housing units in Kibera and establish how they accommodate different arrangement of furniture pieces as well as allow performance of different tasks/functions within a particular space. The research design was the case study model where the research employs the collection and analysis of qualitative data obtained through examination of documents, interviews, observation and taking of photographs. The study was carried out at The Kibera Soweto East Housing Project, Kenya and its residents plus the professionals are involved in the project are the respondents. Findings revealed that the government did try to ensure that the low-cost houses are kept simple, regular/standard by installing standard window and door sizes, eliminating storage facilities apart from the kitchen, installing tiles for the floor, walls for the bathroom and counter top for the kitchen and also installing normal light fixtures, kitchen shelves and sanitary ware. This study findings contributes to informing the development of interior plans and layouts that are ideal for low-cost housing units. Affordability can indeed be achieved in low-cost housing but if the interior plans and layouts are not up to standard then it fails to fulfil its purpose of improving the living standards and quality of life of residents living in these housing units.
Keywords: Low-cost housing units; Interior spaces; Flexibility; Multi-functionality; Interior partitioning; Furniture layouts.